Exploring Hydrocele of the Canal of Nuck in a Mature Woman: Beyond the Norm - Saurav Jha; Sweta Singh; Sajjad Ahmed Khan; Rajat Kumar Shah; Pratick Shrestha; Arjun Kandel; Barsha Baral; Pratik Raj Regmi (Clinical Case Reports)
ABSTRACT Timely diagnosis and surgical intervention are crucial in managing hydrocele of the canal of Nuck. A systematic approach, including thorough examination and appropriate imaging, followed by meticulous surgical technique, ensures successful treatment and favorable long‐term outcomes for patients.